Role of Job Satisfaction on Job Commitment and Value Creation of Management Sciences Academics - Angela Obose Oriazowanlan; Harcourt Ify Nwokocha (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Objective: Job switching intentions and high turnover rates among academics in Nigerian Universities including Southern Nigeria are appalling. The study examined the role of job satisfaction on job commitment and value creation. Research Design & Methods: Five research questions guided the study and two hypotheses were formulated. The study adopted the descriptive survey research design. 150 respondents were selected using a convenient sampling technique. A 46-item structured questionnaire was used as an instrument for data gathering which was rated on four point scale with nominal values. The instrument was scrutinized and found valid. The data gathered was analyzed using mean and standard deviation to address the research questions and determined the respondents’ homogeneity respectively while the null hypotheses were tested with t-test inferential statistics. Findings: The findings revealed that job satisfaction has a great influence on job commitment and value creation. Emphasis was laid on job characteristics such as autonomy, social and environmental factors such as recognition, and appropriate rewards of academics with exceptional skills for value creation as well as motivation by management. Implications & Recommendations: Ingenious academics that are highly talented and gifted should complement affective commitment with continuance commitment and demonstrate their creative prowess and ingenuity to create values for the organization. Also, management should ensure that academics with exceptional work skills are properly rewarded, recognized, and motivated to guarantee their retention, absolute commitment, and effective work performance. Contribution & Value Added: These results provide an overview of the challenges of job satisfaction and poor motivation that could affect their value creation.